The Concept Of “Ahl Al-Sunnah Wa Al-Jamā‘Ah” Revisited - Baharudin Abdul Rahman (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2022)
Understanding about the meaning of “Ahl al-Sunnah wa al-Jamā‘ah” in the hadith which reads: "sa-Taftariqu 'Ummatī' alā Tsalātsatin wa Sab'īna Firqatin al-Nājiyatun Minhā Wāhidatan wa al-Bāqūna halkā," Qāla wa Man al-Nājiyah? Qāla: "Ahl al-Sunnah wa al-Jamā‘ah," Qīla wa Mā al-Sunnah wa al-Jamā‘ah ,? Qāla: "Mā Anā 'Alayhi wa Ashhābī" caused a polemic among Muslim scholars, not only among hadits scholars, but also among the kalām scholars. Using semantic analysis, this study found that the expression “ahl al-sunnah wa al-jamā‘ah” no longer refers to one of the groups of the kalām sect, it refers to those who follow the institutions of the prophet Muḥammad(may peace be upon him) and his shaḥābah. The breakers and heretics, they are no longer considered ahl al-sunnah wa al-jamā‘ah and gain salvation.